234k views
0 votes
What is the answer to this problem 1.5(x + 4) – 3 = 4.5(x – 2)?

2 Answers

0 votes

Expand

1.5x + 6 - 3 = 4.5x - 9

Simplify 1.5x + 6 - 3 to 1.5x + 3

1.5x + 3 = 4.5x - 9

Subtract 1.5x from both sideds

3 = 4.5x - 9 - 1.5x

Simplify 4.5x - 9 - 1.5x to 3x - 9

3 = 3x - 9

Add 9 to both sides

3 + 9 = 3x

Simplify 3 + 9 to 12

12 = 3x

Divide both sides by 3

12/3 = x

Simplify 12/3 to 4

4 = x

Switch sides

x = 4

User Monisola
by
4.6k points
3 votes

Answer:

x = 4

Explanation:

1.5(x + 4) – 3 = 4.5(x – 2)

Distributive property

1.5x + 6 - 3 = 4.5x - 9

1.5x + 3 = 4.5x - 9

1.5x - 4.5x = -9 -3

-3x = -12

x = 4

User Martin Mlostek
by
5.4k points